Analysis of Factors Affecting Hematopoietic Stem Cell Mobilization Efficiency and Early Hematopoietic Reconstruction Indicators during Autologous Peripheral Blood Hematopoietic Stem Cell Transplantation - Shi, Hao; Duan, Yaya; Bu, Xinting (Global Medical Genetics, 2024)
Purpose To analyze the factors affecting the mobilization efficiency of hematopoietic stem cells and hematopoietic reconstruction indicators during autologous peripheral hematopoietic stem cell transplantation.Methods The clinical data of 54 patients who underwent autologous peripheral blood hematopoietic stem cell mobilization and transplantation at Xuzhou Central Hospital from May 2016 to April 2023 were retrospectively analyzed. The gender, age, disease type, mobilization regimen, number of chemotherapy sessions, G-CSF (granulocyte colony-stimulating factor) dosage, and platelet number at the time of collection were also collected. Moreover, the relationship between these indicators with mobilization results and hematopoietic reconstruction was analyzed.Results Results showed that age, disease type, and number of collections were significantly related to the mobilization results (number of CD34+ hematopoietic stem cells). Furthermore, multivariate analysis showed that the number of collections was an independent factor affecting mobilization efficiency. Similarly, age, platelet value at the time of collection, CD34+ stem cell value during collection, white blood cell count, and number of chemotherapy times were significantly related to the time of megakaryocytic hematopoietic reconstruction. Multifactor analysis found that age and platelet count were independent factors affecting the reconstruction time of the megakaryocytic system. However, no factor was related to the time of granulocyte hematopoietic reconstruction.Conclusion Platelet count and age when collecting hematopoietic stem cells are closely related to megakaryocytic hematopoietic reconstruction and are key indicators of early hematopoietic reconstruction after autologous hematopoietic stem cell transplantation.
Keywords: autologous stem cell transplantation; peripheral blood stem cell; platelet value at the time of collection; megakaryocytic hematopoietic reconstruction